AGAMA DAN KONFLIK SOSIAL - Hisyam, Muhammad (P2KK LIPI, 2006)
This article is aimed to seek answers on whether religion can really be the causing factor of conflict, or whether conflict is actually ignited by cultural and other factors. For that purpose, it is also important in this article to see the relation between religion and culture. Religion has potency as peace keeper factor, so as conflict raiser. Exclusivity and claim for truth of a religion has been accused as the main factors that can raise religious conflict. Liberalism movement was trying to reduce these claims for truth among religious beliefs. Exclusive pluralism which was one form of the movement failed since it did not recognize exclusivities of religions which are embedded within each religion. Better approach to pluralism is that respect of religious rights as basic human rights, should then be followed by basic human duties. Despite theoretical issues, the relation between religion and conflict needs further mapping, a method which is also presented in the last part of the article. Kata kunci: Agama, konflik, pluralisme, pemetaan konflik